Analysis and evaluation of sediment pollutants of Euphrates River at Al-Nasiriyah city, south of Iraq - Albaaj, Aliaa Shakir abd alameer (University of Thi-Qar Journal of Science, 2023)
In this work, total phosphorus (TP), total nitrogen (TN) and organic matter (OM) were detected in the sediment of Euphrates River in different period’s time. Then we did the analysis and the characterization of these pollutants for this river. In addition, . The findings of this study showed that the sediment levels of total phosphorus in Euphrates river were 2.05 ~ 6.50 mg/g, 1.65 ~ 3.17 mg/g and 0.71 ~ 0.93 mg/g   the sediment levels of total nitrogen were 5.06 ~ 8.98 mg/g, 6.07 ~ 8.56 mg/g and 5.02 ~ 7.99 mg/g. Also, organic matter levels in sediment were 40.54 ~ 70.1 mg/g, 58.70 ~ 85.63 mg/g and 11.32 ~ 30.17 mg/g in Clearly, from that analysis and comparison of pollutants level, the sediment of Euphrates River is the main source of contamination. This may be able to result from increasing the human activities and the increment of industrial actions in this region.